Studies on the Effect of Typha angustata (Reed) on the Removal of Sewage Water Pollutants - S. Kalaivani, D. Ramamoorthy* and (Journal of Phytology, 2011)
Rhizoremediation is the process in which exudates derived from the plant root stimulate the survival and activity of the soil bacteria and fungi, resulting in a more efficient degradation of water soluble pollutants in rhizosphere. The present study was carried out in the zone of naturally growing reed plants (reed zone) and zone not occupied by Typha angustata along the banks of a domestic sewage pool in one of the residential areas of Puducherry. The lower levels of biochemical oxygen demand(BOD) and total dissolved solids (TDS) and lower concentrationÃ‚Â of heavy metals such as lead, manganese, zinc and copper and higher level of dissolved oxygen (DO) wereÃ‚Â noticed in the Reed (Typha angustata) root zone compared to non reed root zone. Though all the six bacterial species under five types of bacterial populations and eight types of fungal populations were found in both the zones, the numbers of colonies were found to be more in reed zone than non reed root zone. This suggests that the rhizosphere of Typha angustata has a direct influence on the composition and density of soil microbial community. Exudates of Reed plant caused an increase in the metabolic activity of microbes of the rhizosphere and transformed the organic and inorganic pollutants into harmless compounds. It is concluded that Typha root zone with its myriad of microbes served as a bio-bed which has the potential to reduce the BOD and TDS levels of sewage water, decrease the concentration of heavy metals and increase dissolved oxygen in the water body.